Non‐alcoholic fatty liver disease – histological scoring systems: a large cohort single‐center, evaluation study. Issue 11 (27th October 2017) - Rastogi, Archana; Shasthry, Saggere Muralikrishna; Agarwal, Ayushi; Bihari, Chhagan; Jain, Priyanka; Jindal, Ankur; Sarin, Shiv
Abstract : Non‐alcoholic fatty liver disease (NAFLD) is an increasingly common cause of chronic liver disease. Till date, liver biopsy remains the gold standard for identification and quantification of the wide histological spectra of NAFLD. Histological scorings are very useful and widely applied for the diagnosis and management in clinical trials and follow‐up studies of non‐alcoholic steatohepatitis (NASH). However, in view of scarce published literature, there is a need to evaluate them in large cohort of NAFLD. This study was aimed to evaluate the two histological scoring systems (NAS‐CRN, SAF) in the diagnosis of NAFLD and to assess the role of histological characteristics as injury markers in NAFLD. Retrospective histological study of liver biopsies of 1000 patients diagnosed as NAFLD, between 2010 and 2016, was conducted. Histopathologic evaluation and semiquantiative scoring based on NAS‐CRN and SAF algorithm and their correlation with serum aminotransferase and fibrosis were performed. Liver biopsies were classified according to the NAS‐CRN scoring, as NAS <3 (not NASH) in 72 (7.2%), NAS 3–4 (borderline NASH) in 310 (31%), and NAS ≥5 (definite NASH) in 618 (61.8%), and SAF classified 117 (11.7%) not NASH and 883 (88.3%) definite NASH. There was excellent concordance for definite NASH and not NASH; however, 88.06% of borderline NASH was classified as NASH by SAF. 76.39% by NAS and 78.63% by SAF algorithm who were diagnosed as not NASH showed the presence of fibrosis; however, higher stages of fibrosis were significantly more prevalent in definite NASH, excluding burnt‐out cirrhosis. Serum ALT was significantly associated with increasing stages of fibrosis (p < 0.001) and the three categories (not NASH, borderline NASH, and definite NASH) when classified as with/without fibrosis (p < 0.001). Steatosis of higher grades, more ballooned cells, and more foci of Lobular Inflammation were found in significantly higher proportion of patients with NASH (p < 0.001), with higher fibrosis stages (p < 0.001) and higher serum ALT levels (p < 0.001). NAFLD classifications based on histological scoring NAS‐CRN and SAF algorithm are concordant for the category of definite NASH and not NASH, while borderline NASH shows discrepant interpretation. There was highly significant correlation between the NAS and SAF categories with high grades of histological characteristics, with serum ALT and with higher stages of fibrosis. Exclusion of fibrosis is a limitation with both scores.